The Effect of Addition Fermented Dairy-Waste Water Sludge By Aspergillus Niger in Ration on Growth Performance and The Caecal Microbial of Broiler - Marlina, Eulis Tanti; Balia, Roostita Lobo Lobo; Lukman, Denny Widaya (ANIMAL PRODUCTION, 2019)
Dairy Wastewater Sludge (DWS) is sediment from milk processing. Nutritional content of DWS can be used as feed ingredients. The effects of nutrition in DWS are tested on the growth of broiler as well as its specific impact on the development of microflora on broiler digestion. The research methods used experimental design. Tapioca by-product (onggok) is used as DWS binder while Aspergillus niger fermentation is applied to improve nutritional content. The rate of addition fermented DWS in the ration was evaluated through measuring weight gain for 35 days and microflora quality in the cecum by counting the number of non-pathogenic and pathogenic bacteria in the cecum at the end of the research period. The research data were analyzed by ANOVA with Duncan's multiple range test. The results showed that the addition of 20% fermented DWS in rations resulted in the highest body weight gain and could suppress the growth of pathogenic bacteria (Salmonella spp., E. coli, and Enterobacteriaceae) in caecal. The ratio of non pathogenic and pathogenic bacteria increased proportional to the addition of fermented DWS levels in the ration. Different caecum weight of broiler with different fermented DWS levels was a reprentation of microorganism activity in caecum. This condition can illustrate the good health status of livestock so as to optimize the growth of broiler.